A situation analysis of inter‑professional education and practice for ethics and professionalism training at Makerere University College of Health Sciences - Byakika‑Kibwika, Pauline; Kutesa, Annet; Baingana, Rhona; Muhumuza, Christine; Kitutu, Freddy Eric; Mwesigwa, Catherine; Nabirye Chalo, Rose; Sewankambo, Nelson K. (BMC research notes, 2015)
Students at Makerere University College of Health Sciences (MakCHS) are introduced to ethics and professionalism using the inter-professional education (IPE) model. Ethics and professionalism should be running themes throughout succeeding years of study during which students are expected to develop qualities and skills for future inter-professional practice (IPP). We performed a situation analysis of IPE and IPP among students and teaching health professionals at MakCHS to guide development of a relevant training curriculum of ethics and professionalism. Methods: A cross sectional study with quantitative and qualitative methods which included questionnaires, focus group discussions and key informant interviews. Results: We interviewed 236 undergraduate students (148, 63 % male) and 32 teaching health professionals (25, 78 % male). Two hundred fifteen (91 %) students indicated they had joint learning activities with students of other professions and 166 (70 %) stated there was benefit in having an IPE model training curriculum. Most students (140, 59 %) strongly agreed that learning with other students will make them more effective members of the health team. Whereas the respondents reported inter professionalism as being well articulated in their course curricula, more than half said IPE is only implemented in the pre-clinical years of study. They noted that IPE and IPP concepts were not well programmed, health professionals engaged in teaching had poor attitudes towards IPE and IPP, there were limited numbers of skilled health care workers to implement IPP and there was poor communication between students and teaching health professionals. Majority of teaching health professionals noted challenges in implementation of IPE such as poor coordination and large student population and major factors influencing ethics and professionalism in healthcare such as limited government support, low pay for the health care workers, disrespect and lack of appreciation of the health workers by the public. Conclusions: Our findings demonstrate that IPE, IPP, ethics and professionalism are not emphasized in the clinical years of study at MakCHS. We recommend increased sensitization on the concepts of IPE and IPP plus enhanced mentorship for both students and teaching health professionals. Innovative strategies of implementation of IPE and IPP for training in ethics and professionalism must be introduced.
Keywords: Inter-professional education; Practice; Ethics; Professionalism; Makerere University